Multiple Criteria Decision Analysis in HDMI Splitter Selection Using Complex Proportional Assessment Method - Arisantoso Arisantoso; Teddy Mantoro; Akeem Olowolayemo; Abdullah Alkalbani (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2022)
High-Definition Multimedia Interface (HDMI) technology is used for devices such as HDTVs, Projectors, and DVD players. One HDMI cable can only connect one device, even though, when needed, one computer or laptop can be displayed on several televisions or projectors using HDMI Splitter. HDMI Splitter is an accessory that displays content on multiple screens. HDMI Splitter has been circulated with various brands that offer different capabilities and specifications. Therefore, Therefore, thorough consideration is needed in choosing the right HDMI Splitter. This study aims to build a decision support system with the Multiple Criteria Decision Analysis (MCDA) approach using Complex Proportional Assessment (COPRAS). The COPRAS method solves the selection problem by calculating the utility level of alternatives, which shows the extent to which an alternative is better or worse than other alternatives through a comparison process. Based on existing studies, the utility values of each alternative were obtained, namely: Robot HDMI Splitter producing a value of 53.73%, Vention HDMI Splitter producing a value of 65.63%, Bafo HDMI Splitter producing a value of 97.13, and PX HDMI Splitter producing a value of 100%. Hence, based on testing through the black box, the best alternative is PX HDMI Splitter.